Terapi modulator CFTR yang ditargetkan pada anak-anak dengan fibrosis kistik: Tinjauan sistematis terhadap uji klinis terkontrol acak yang mengevaluasi hasil klinis berdasarkan genotype - Malkan, Muhamad Ibnu; Negara, R. Moch Satrio Siliwangi Syariffatihmulia (Maliki Interdisciplinary Journal, 2026)
Cystic fibrosis (CF) is a chronic, progressive genetic disorder with clinical manifestations beginning early in life. The development of cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapies has shifted treatment strategies by targeting the underlying molecular defect. However, clinical responses vary widely in pediatric patients and are influenced by CFTR genotype, age at therapy initiation, and the type of modulator used. This systematic review aims to assess the effectiveness and safety of CFTR modulator therapy in children with cystic fibrosis based on genotype-specific clinical outcomes from randomized controlled trials. A systematic literature search was conducted in major electronic databases to identify randomized controlled trials involving CF patients aged ≤18 years. Interventions included CFTR potentiators, correctors, or combination therapies, compared with placebo or standard care. Outcomes evaluated included pulmonary function, pulmonary exacerbations, sweat chloride concentration, nutritional status, and safety profiles. Data were synthesized narratively with emphasis on genotype-based responses. The effectiveness of CFTR modulators was genotype dependent. Ivacaftor provided significant clinical benefits in patients with gating mutations, while combination therapies in those with the F508del mutation showed moderate improvement. Triple-combination therapy demonstrated the most consistent benefits, particularly in sensitive parameters such as the lung clearance index. Early initiation of therapy may modify the natural disease course. CFTR modulator therapy represents a move toward precision medicine in pediatric cystic fibrosis, with genotype-based treatment selection and early intervention being key determinants of clinical benefit.